2004
DOI: 10.1111/j.0022-1112.2004.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on otolith composition in Pomatomus saltatrix, an estuarine piscivore

Abstract: To test the hypothesis that elemental composition of otoliths (sagittae) could be influenced by differences in natural prey type, young-of-the-year bluefish Pomatomus saltatrix were captured immediately after their migration from oceanic waters into mid-Atlantic Bight estuaries and fed either shrimp, Crangon septemspinosa and Palaemonetes spp. or fish Menidia menidia under similar temperature and salinity regimes in two separate 60 day experiments. Unlimited rations of fish and shrimp prey were provided in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 35 publications
6
75
0
Order By: Relevance
“…2). SigniWcant eVects on strontium and barium uptake into otoliths were found in blueWsh, P. saltatrix (Buckel et al 2004) fed on Wsh versus shrimp diets. Contents of Sr and Ba reached values from 110.4 ppm Sr and 0.996 ppm Ba in Wsh to 421.6 ppm Sr and 3.523 ppm Ba in shrimp diet.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2). SigniWcant eVects on strontium and barium uptake into otoliths were found in blueWsh, P. saltatrix (Buckel et al 2004) fed on Wsh versus shrimp diets. Contents of Sr and Ba reached values from 110.4 ppm Sr and 0.996 ppm Ba in Wsh to 421.6 ppm Sr and 3.523 ppm Ba in shrimp diet.…”
Section: Discussionmentioning
confidence: 99%
“…Element composition of biogenic aragonites is thought to depend mainly on physicochemical properties of the surrounding water (Campana 1999). Nevertheless, it has been repeatedly reported that endogenous factors such as diet might have an eVect on the element compositions of Wsh otoliths (Limburg 1995;Farrell and Campana 1996;Gallahar and Kingsford 1996;Buckel et al 2004) as well as cephalopod statoliths (Zumholz et al 2006), since cations entering the inner ear endolymph via the blood circuit can originate either from branchial or intestinal uptake (Campana 1999). Previous investigations on the importance of food on element incorporation into otoliths were highly ambiguous.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations